Key management issues of heavy menstrual bleeding in adolescents and young women - Elena Vitalievna Uvarova (IP Berlin A.V., 2022)
Despite high prevalence of heavy menstrual bleeding (HMB) in adolescents and young women, most recommendations are not specific for this population, which makes the diagnosis and management challenging. Gynecologists should be able to establish underlying causes of HMB, which most common are nonstructural in adolescents, and the severity of bleeding, to provide early diagnosis, using appropriate therapy for improving quality of life and iron deficiency prevention. First line management consists of hormonal therapy approved for HMB treatment, capable to normalize menstrual blood loss and iron metabolism parameters.